Critical Book Review: Maritime Security: The Unlawful Dimension - Pandey, Shivam Kumar (International Journal of Psychosocial Rehabilitation, 2019)
Dr Prabhakaran Paleri concluded his tenure as the Director General of the Indian Coast Guard in 2006. Currently, he holds the esteemed position of professor and advisor at the National Institute of Technology, Calicut, while also serving as a non-official part-time director at the Cochin Shipyard. In addition, the individual has demonstrated authorship of various publications, including books, papers, and articles, about strategic and management topics. Furthermore, they have engaged in scholarly endeavours as a visiting research scholar domestically and internationally, including in India. Maritime security has been a prominent topic over the past decade, especially after the 9/11 terrorist attacks on the USA. While there were existing traditional and non-traditional maritime security concerns, the attack prompted governments to take concerted action. Despite the extensive literature available on the topic for over ten years, most of it has been subpar, lacking in-depth knowledge. Only a limited number of works have made valuable contributions to our comprehension of the issues at hand. This Book falls into the latter category, as it effectively incorporates the crucial legal aspect of maritime security issues, a facet frequently overlooked in other written works. The study of maritime security has increasingly focused on the complexities of the ocean, which has served as a battleground since ancient times. However, there has been a significant shift in this concept in recent years. In the future, maritime security must be viewed as an integral part of national security rather than an independent concept.